E-module on Ethnobotany of Medicinal Plants to Improve Scientific Literacy and Cognitive Abilities of Junior High School Students - Alivinda Aulia Safira Musyarofah; Rif'ati Dina Handayani; Sulifah Aprilya Hariani (Universitas Pendidikan Ganesha, 2025)
The purpose of this study is to create an e-module on medicinal plant ethnobotany to improve students' scientific literacy and cognitive abilities. This research is an R&D development project utilizing a 4D development model (Define, Design, Develop, Disseminate). However, it is still in the development stage, with the aim of implementation for 7th-grade junior high school students. Data collection for e-module validation was conducted by distributing validation sheets to material experts, media experts, and users (8 teachers). Data were analyzed using quantitative descriptive techniques, with the percentage results adjusted to the corresponding assessment category. The results showed a material validation of 82.14% and a media expert validation of 95%, indicating that the medicinal plant ethnobotany e-module is suitable for educational purposes. Pretest and posttest validation of scientific and cognitive literacy fall into the very valid category, with validation percentages of 89.9% for the scientific literacy pretest, 88.3% for the scientific literacy posttest, 81.05% for the cognitive pretest, and 87.1% for the cognitive posttest. These results indicate that the test instrument used to measure students' scientific literacy and cognitive abilities is well-structured and applicable in the classroom. This demonstrates that the e-module is highly suitable for use in seventh-grade science instruction, specifically in the chapter on the classification of living things. This research implies that the e-module's flexibility and relevance to students' daily lives make it an effective assessment tool for measuring students' scientific literacy and cognitive abilities.